2014
DOI: 10.1021/ic501139w
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Chemical Sorcery of “GaI”: Benefits of Solid-State Analysis Aiding in the Synthesis of P→Ga Coordination Compounds

Abstract: The differing structures and reactivities of "GaI" samples prepared with different reaction times have been investigated in detail. Analysis by FT-Raman spectroscopy, powder X-ray diffraction, (71)Ga solid-state NMR spectroscopy, and (127)I nuclear quadrupole resonance (NQR) provides concrete evidence for the structure of each "GaI" sample prepared. These techniques are widely accessible and can be implemented quickly and easily to identify the nature of the "GaI" in hand. The "GaI" prepared from exhaustive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…This dearth in examples could be attributed to the fact that more electron density is necessary to help soften the repulsive Coulombic force. Instead of oxidation to tetrel(III), a tetrel(I) species could be targeted using L‐type ligands, which has been a useful approach in accessing Ga II 1,2‐dications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dearth in examples could be attributed to the fact that more electron density is necessary to help soften the repulsive Coulombic force. Instead of oxidation to tetrel(III), a tetrel(I) species could be targeted using L‐type ligands, which has been a useful approach in accessing Ga II 1,2‐dications …”
Section: Introductionmentioning
confidence: 99%
“…Instead of oxidation to tetrel(III), at etrel(I) speciesc ould be targeted using L-type ligands, which has been au seful approach in accessing Ga II 1,2-dications. [17,18] There are ah andful of compounds containing heavy tetrel elements with an oxidation state of (I). Aside from some exceptions, [19][20][21] the field has been dominated by two main classes, the heavy alkyne analogues [22][23][24][25] and those supported by monoanionic chelating ligands (A-E in Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1b], The clusters isolated from corresponding reactions with Li(thf) 3 (R 1 ) depended on the “GaI” composition , . It was also demonstrated that the products resulting using “GaI“ vary with time of ultra‐sonification , . “GaI” is insoluble in organic solvents or decomposes under disproportionation into Ga 0 and GaI n · Do (n = 2,3) with donor solvents (Do), making the reactions poorly selective.…”
Section: Introductionmentioning
confidence: 99%
“…[8,24] It was also demonstrated that the products resulting using "GaI" vary with time of ultra-sonification. [15,25] "GaI" is insoluble in organic solvents or decomposes under disproportionation into Ga 0 and GaI n ·Do (n = 2,3) with donor solvents (Do), [26] making the reactions poorly selective. The isolation of Ga 3 I 5 (PEt 3 ) 3 by addition of P(Et) 3 to "GaI" demonstrates possible disproportionation pathways.…”
mentioning
confidence: 99%
“…Stabilizing gallium in its low oxidation states (<III) has been an objective since the 1,930 s. (ref. 13 ) Subvalent gallium halides Ga I [Ga III X 4 ] (X=Cl, Br and I) 14 , ‘GaI' (refs 15 , 16 ) and metastable, donor stabilized Ga I Cl solutions 9 are important milestones and to this day used as starting material for further Ga I chemistry: for example, arene- 17 , Cp x -complexes (Cp x : Cp=C 5 H 5 and Cp*=C 5 Me 5 ), (ref. 18 ) N-heterocyclic carbene (NHC) analogues 19 20 of Ga I , or metalloidal gallium clusters 7 .…”
mentioning
confidence: 99%